2021
DOI: 10.3390/jcm10173883
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Prostate Cancer Recurrence Assessed by 68Ga-PSMA-11 PET/CT in Men Treated with Primary Local Therapy

Abstract: Imaging plays a vital role in detecting the recurrence of prostate cancer (PCa) to guide the choice of salvage therapy. Gallium-68 prostate-specific membrane antigen positron-emission tomography/computed tomography (68Ga-PSMA-11 PET/CT) is useful for detecting PCa recurrence. We assessed the pattern of PCa recurrence stratified by serum prostate-specific antigen level and type of primary local treatment in men with biochemical recurrence (BCR) after primary local therapy with radical prostatectomy or external … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Hence, a significant proportion remains with a relevant window for a definitive cure ( 7 ). Similar figures are confirmed by recent PET-PSMA imaging studies, as more than half of recurrences are localized to the prostatic bed only ( 8 , 9 ).…”
Section: Introductionsupporting
confidence: 86%
“…Hence, a significant proportion remains with a relevant window for a definitive cure ( 7 ). Similar figures are confirmed by recent PET-PSMA imaging studies, as more than half of recurrences are localized to the prostatic bed only ( 8 , 9 ).…”
Section: Introductionsupporting
confidence: 86%
“…Lawal et al (2021) identified 247 patients with BCR post external beam radiotherapy (EBRT) or RP. When comparing EBRT and RP, the site of recurrence on PSMA PET-CT was 67.4% vs. 43.4% at the prostate bed, 17.4% vs. 16.5% at SV, 37.2% vs. 34.7% in pelvic nodes and 9.3% vs. 18.3% to bone, respectively, [ 117 ]. Similar results were demonstrated in a review by Armstrong et al (2020), which also found that patients who underwent RP had a lower local recurrence rate than those who had radiotherapy (21.3% vs. 63.3%) but shorter time from initial therapy to recurrence (27.7 months vs. 54.6 months).…”
Section: Role Of Psma Pet-ct In Biochemical Recurrence After Curative...mentioning
confidence: 99%
“…At first glance, these figures do not seem justified considering that half of men with radioresistant PCa have not experienced metastases by 5 yr, which thus represents a significant window for cure. More recently, prostate-specific membrane antigen (PSMA) positron emission tomography (PET) imaging studies revealed that more than half of recurrences are confined to the prostate [8] , [9] .…”
Section: Introductionmentioning
confidence: 99%